Residential Factors of Pneumonia: A Literature Review (Jurnal Ilmu Kesehatan Masyarakat, 2019)
Pneumonia remains a problem among children around the world and become deadly disease among children under five years of age. It contributed 16% of 5,6 millions death of children.UNICEF stated that 24000 children were dead because of pneumonia each day. this study aim was to explain residential factors of Pneumonia. This was a literature review from some journals and books. unadequate healthy house take part in spreading Pneumonia among children. Improving residential environment could be prioritized to prevent Pneumonia spreading bigger. Keywords: children pneumonia, residential